Anmeldelser - Egeland Hansen, Finn (Danish Yearbook of Musicology, 2008)
Review of: Anders Meng: Temporal Feature Integration for Music Organisation. Kgs. Lyngby, Danmarks Tekniske Universitet, 2006. Peter Ahrendt: Music Genre Classification Systems – A Computational Approach. Kgs. Lyngby, Danmarks Tekniske Universitet, 2006.